A review of organic inputs to inform soil health advice for African smallholder farmers: localization matters - Weldesemayat, S. Gudeta; Stewart, Zachary P.; Odhong, Jonathan A.; Mhlanga, Blessing; Amede, Tilahun; Aynekulu, Ermias; Thierfelder, Christian; Marenya, Paswel P.; Dittmer, Kyle M.; Kamaluddin Tijjani Aliyu; Chikowo, Regis; Chiduwa, Mazvita S.; et al. (Springer, 2025)
African smallholder farming systems are complex, diverse and locally adapted, but guidance is lacking on how farmers can make informed choices of the type of organic inputs to suit their farm conditions. In this review we aimed to provide a synthesis of actionable information on ex situ and in situ organic resources and decision support tools to facilitate evidence-based choices by smallholders in cereal production systems in sub-Saharan Africa.